Investigation of Heat Exchange Processes during Thermal Decontamination of Industrial Sewage Water in Foam Generating Reactors - A. V. Kotchetkov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2003)
Model for calculation of combustion process of combustible foam flow which has been obtained by means of natural gas sparging of sewage water containing organic matter is proposed in the paper. The model makes it possible to determine factors that effect on changes in temperature profile of combustion zone and thickness of zone reaction.